VS-4718 Antagonizes Multidrug Resistance in ABCB1- and ABCG2-Overexpressing Cancer Cells by Inhibiting the Efflux Function of ABC Transporters - Ji, Ning; Yang, Yuqi; Cai, Chao-Yun; Lei, Zi-Ning; Wang, Jing-Quan; Gupta, Pranav; Teng, Qiu-Xu; Chen, Zhe-Sheng; Kong, Dexin; Yang, Dong-Hua (Frontiers in Pharmacology, 2018)
Overexpression of ATP-binding cassette (ABC) transporters is one of the most important mechanisms responsible for multi-drug resistance (MDR). VS-4718, a tyrosine kinase inhibitor targeted focal adhesion kinase (FAK) with a potential anticancer effect, is currently in clinical development. In this study, we investigated whether VS-4718 could reverse MDR mediated by ABC transporters, including ABCB1, ABCG2, and ABCC1. The results showed that VS-4718 significantly reversed ABCB1- and ABCG2-mediated MDR, but not MDR mediated by ABCC1. Treatment of VS-4718 did not alter the protein level and subcellular localization of ABCB1 or ABCG2. Mechanism studies indicated that the reversal effects of VS-4718 were related to the attenuation of the efflux activity of ABCB1 and ABCG2 transporters. ATPase study indicated that VS-4718 stimulated the ATPase activity of ABCB1 and ABCG2. Docking study showed that VS-4718 interacted with the substrate-binding sites of both ABCB1 and ABCG2, suggesting that VS-4718 may affect the activity of ABCB1 and ABCG2 competitively. This study provided a novel insight for MDR cancer treatment. It indicated that combination of VS-4718 with antineoplastic drugs could attenuate MDR mediated by ABCB1 or ABCG2 in ABCB1- or ABCG2-overexpressing cancer cells.